Narrative Mode and Theological Claim in Johannine Literature Essays in Honor of Gail R. O'Day. - Huber, Lynn R. (Biblical Scholarship in North America Ser., 2021)
In this collection of essays and sermons on the Gospel of John and Revelation, friends, colleagues, and former students of Gail R. O'Day explore and extend the possibilities raised by her work in her groundbreaking study Revelation in the Fourth Gospel. The essays engage with both historical contextualization and literary analysis to identify the rhetorical features that ancient readers might have apprehended, while the sermons explore how the literary shape of the text can inform preaching through attention to the narrative modes of the text. Contributions from Yoshimi Azuma, Teresa Fry Brown, Patrick Gray, Lynn R. Huber, Susan E. Hylen, Karoline M. Lewis, Thomas G. Long, Veronice Miles, Vernon K. Robbins, Gilberto A. Ruiz, Ted A. Smith, and William M. Wright IV thematize the importance of narrative approaches and the diverse ways they can be employed.